A invenção do eu em Angústia, de Graciliano Ramos - Pessoa, Katia Regina (2008)
This study has for objective to investigate the invention of the I in Angústia, by Graciliano Ramos, to the light of the autobiographical gender in your unfolding: the autobiographical fiction, tends in view that who writes is not the real author, but your other fictional. Such unfolding is correlated with two groups of images that repeat continually inside the report, be in the memory that registered them, be in the plan of the own deed. The first of them corresponds to the element snake, that symbolizes coalition, seduction and asphyxia. The second refers to the mouse and it represents dissolution and contamination - elements these that, inserted in the discursive field, starting from the writing strategy used by the author-narrator Luís da Silva, they configure the act scriptural. The analysis methodology consisted of picking the reverberations of those two nuclei of images through the selection of fragments of the romance, in way to build the personal micro-narratives: sub-groups that pick up the game ideas, seduction, asphyxia, death and fracture disseminated by the deed and capable, also, of providing the possible association of last memories to the narrative of the present, through the projection by image. In conclusion, was possible to detect the degree of density of the textual plot that, starting from the spiraled unfolding of the two groups of images, it reconstructed a deed seductive, suffocating and lacerated, propitiated by the snake/rope, as underground and cut into pieces, suggested by the image of the mice, creatures that travel and populate the dark and hidden songs of the undergrounds of Angústia freely. Before that, the ficcional author want, through the imagination and of the conjunction of fragments, your own invention